High Levels of Antimicrobial Coresistance among Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae - Schwaber, Mitchell J. (American Society for Microbiology, 2005)
We compared the susceptibility of 312 extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae isolates with that of 1,216 ESBL nonproducers. Of ESBL producers, 25% were susceptible to gentamicin, 30% to trimethoprim-sulfamethoxazole, 41% to ciprofloxacin, and 60% to piperacillin-tazobactam. ESBL nonproducers were more often susceptible to these agents. ESBL-producing Enterobacteriaceae represent a major source of resistance to various antibiotics.